Cognitive and physical factors affecting daily function in Alzheimer's disease: A cross‐sectional analysis. (7th May 2018) - Yu, Fang; Chen, Yan; Mathiason, Michelle A.; Wan, Qiaoqin; Lin, Feng V.
Abstract: Understanding the factors affecting activities of daily living (ADL) is important in Alzheimer's disease (AD), because decline in ADL contributes to many poor health outcomes. Existing studies often investigate the factors in isolation without a theoretical framework. The purpose of the present study was to provide preliminary results on how cognition, physical performance, and behavioral and psychological symptoms of dementia mediate the relationship of aerobic fitness and ADL in AD. A cross‐sectional analysis was used ( n  = 28: average age 78 [8] years, education 16 (3) years, Mini‐Mental State Examination scores 20 [4]). The results showed that aerobic fitness is not linked to ADL directly, and its association with ADL was mediated by physical performance and global cognition. Our findings provide preliminary support for aerobic fitness as a potential therapeutic target, as enhanced aerobic fitness could simultaneously modify other factors affecting ADL. Nurses are in a unique position for coordinating exercise safety assessment and prescription and educating older adults with AD about exercise participation.